A controlling alkalmazásának lehetőségei a kis- és középvállalkozások versenyképességének a növelésében - Sütő Dávid (2016)
In Hungary, 99.9% of all operating enterprises are small- and medium sized enterprises. Within the corporate sector, the micro-, small- and medium-sized enterprises have significant weight independently of the economic development and management culture, having regard also to their employment headcount rate and financial performance. The livelihood and welfare of large sections of society depend on the survival and performance of the enterprises belonging to the sector. In order to overcome this obstacle and to be able to meet the demands created by the globalization, international competition and the society, the small- and medium-sized enterprises should align their strategy with their environment. The most effective tool of it is the controlling that the SMEs can use as a support in order to increase the efficiency of their managerial decisions. In my treatise, I examine the opportunities to measure the performance of small- and medium-sized enterprises.